PERBANDINGAN SOSIAL DAN EMOSI ANAK USIA PRASEKOLAH YANG MENGIKUTI DAN TIDAK MENGIKUTI PENDIDIKAN ANAK USIA DINI - Asmarita Asmarita; Hamid Abdurrahman; Utami Agnita (Bali Health Published Journal, 2019)
Background: Social and emotional development of young children is affected by many stimulating factors, and one of those factors is early childhood education however, not all preschool children have the opportunity to attend early childhood education. This study was aimed at comparing children’s social and emotional development of those who attend and do not attend early childhood education. Method: This comparative study was carried out using cross sectional approach among 72 participants divided into 2 groups: 36 participants who attend early childhood education and 36 participants who do not attend early childhood education. Consecutive sampling technique was applied to select samples. Results: Non-parametric statistical test employed was Mann Whitney test, whose comparison value of children attending and not attending early childhood education was Pvalue 0.000; the emotional comparison value was Pvalue 0.040, so it can be concluded that there were differences in social and emotional development between children who attend early childhood education and those who do not attend early childhood education. Conclusion: Early childhood education can help stimulate development on children. Parents should pay more attention to their children’s social and emotional development, whereas if parents cannot be the medium to support children’s social and emotional development, they should engage their children to early childhood education.